Foundations of Software Science and Computation Structures 26th International Conference, FoSSaCS 2023, Held as Part of the European Joint Conferences on Theory and Practice of Software, ETAPS 2023, Paris, France, April 22-27, 2023, Proceedings - Kupferman, Orna; Sobocinski, Pawel (Lecture Notes in Computer Science, 2023)
This open access book constitutes the proceedings of the 26th International Conference on Foundations of Software Science and Computational Structures, FOSSACS 2023, which was held during April 22-27, 2023, in Paris, France, as part of the European Joint Conferences on Theory and Practice of Software, ETAPS 2023. The 26 regular papers presented in this volume were carefully reviewed and selected from 85 submissions. They deal with research on theories and methods to support the analysis, integration, synthesis, transformation, and verification of programs and software systems.